Use of waste recycling coal bottom ash and sugarcane bagasse ash as cement and sand replacement material to produce sustainable concrete - Bheel, N. (Springer Science and Business Media Deutschland GmbH, 2022)
Concrete is widely used as a building material all over the world, and its use is increasing the demand of cement and sand in the construction industry. However, the limited resources and environmental degradation are driving scientists to develop alternative materials from vast volumes of agro-industrial wastes as a partial replacement for conventional cement. In the manufacture of concrete, cement is a major binding resource. This study looked into recycling agro-industrial wastes into cement, such as sugarcane bagasse ash (SCBA), coal bottom ash (CBA), and others, to create sustainable and environmentally friendly concrete. This study aims to see how the combined effects of agricultural by-product wastes affected the characteristics of concrete. SCBA is used to replace fine aggregate (FA) ranging from 0 to 40 by weight of FA, while CBA is used to replace cement content ranging from 0 to 20 by weight of the total binder. In this case, a total of 204 concrete samples (cubes and cylinders) are made using a mixed proportion of 1:1.5:3 and a water-cement ratio of 0.54. Workability, density, water absorption, and mechanical characteristics in terms of compressive and splitting tensile strengths were examined in this study. In addition, for each mix percentage, the total embodied carbon was determined. Workability, density, and water absorption were found to be considerably decreased when CBA and SCBA concentration increased. Due to the pozzolanic nature of CBA and SCBA, an increase in compressive and splitting tensile strengths were seen for specific concrete mixtures, and further addition of CBA and SCBA, the decrease in strength. The embodied carbon of SCBA has augmented the total embodied carbon of concrete, though it can be seen that C15S40, which comprises of 15 CBA and 40 SCBA, is the optimum mix that attained tensile and compressive strength by 3.05Â MPa and 28.75Â MPa correspondingly, with a 4 reduction in total embodied carbon. Â© 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.